Applications of Network Pharmacology in Traditional Chinese Medicine Research. (14th February 2020) - Zhou, Zhuchen; Chen, Bing; Chen, Simiao; Lin, Minqiu; Chen, Ying; Jin, Shan; Chen, Weiyan; Zhang, Yuyan
Abstract : Human diseases, especially infectious ones, have been evolving constantly. However, their treatment strategies are not developing quickly. Some diseases are caused by a variety of factors with very complex pathologies, and the use of a single drug cannot solve these problems. Traditional Chinese Medicine (TCM) medication is a unique treatment method in China. TCM formulae contain multiple herbs with multitarget, multichannel, and multilink characteristics. In recent years, with the flourishing development of network pharmacology, a new method for searching therapeutic drugs has emerged. The multitarget action in network pharmacology is consistent with the complex mechanisms of disease and drug action. Using network pharmacology to understand TCM is an emerging trend.